2019
DOI: 10.1021/acs.biochem.9b00275
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Granulin Domain Peptides Bind to Pro-Cathepsin D and Stimulate Its Enzymatic Activity More Effectively Than Progranulin in Vitro

Abstract: Progranulin (PGRN) is an evolutionarily conserved glycoprotein associated with several disease states, including neurodegeneration, cancer and autoimmune disorders. This protein has recently been implicated in the regulation of lysosome function, whereby PGRN may bind to and promote the maturation and activity of the aspartyl protease cathepsin D (proCTSD -inactive precursor, matCTSD -mature, enzymatically active form). As the full-length PGRN protein can be cleaved into smaller peptides, called granulins, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
0
34
2
Order By: Relevance
“…1c). CTSD has also been implicated in multiple neurodegenerative diseases and was previously demonstrated to associate with PGRN, affecting both CTSD levels and activity [14,[34][35][36][37][38][39]. One recent study reported that prolonged incubation (16 hours) of PGRN with CTSD at pH 3.5 can lead to PGRN cleavage, although low molecular weight granulin-sized bands were not observed [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1c). CTSD has also been implicated in multiple neurodegenerative diseases and was previously demonstrated to associate with PGRN, affecting both CTSD levels and activity [14,[34][35][36][37][38][39]. One recent study reported that prolonged incubation (16 hours) of PGRN with CTSD at pH 3.5 can lead to PGRN cleavage, although low molecular weight granulin-sized bands were not observed [20].…”
Section: Resultsmentioning
confidence: 99%
“…1a). Fragments consisting of multiple granulins have also been previously described [12,13], and these multi-granulin fragments (MGFs) exert biological activities as well [14]. PGRN is secreted into the extracellular matrix where proteases, such as neutrophil elastase, may process PGRN [6,8,15].…”
Section: Introductionmentioning
confidence: 99%
“…A few have also argued that increased proteolysis of PGRN as a reason for haploinsufficiency, which will directly correlate with increased GRN levels (57). A more recent study established that more effective proteolytic processing of cathepsin D, an aspartyl protease that is known to cleave PGRN, occurs in the presence of GRNs (92), which seem to support the idea that generation of GRNs to be the reason for decreased availability of PGRN. Results presented in this study establish a potential mechanism by which GRNs directly interact with TDP-43CTD and modulate the latter's ability to aggregate and/or phase separate (Fig 6).…”
Section: Discussionmentioning
confidence: 96%
“…In vitro , progranulin added to recombinant cathepsin D protects this protein from high temperature-induced denaturation/degradation ( Beel et al, 2017 ). Progranulin stabilizes the propeptide of cathepsin D, promoting autocatalysis at the active site ( Butler et al, 2019 ). In the absence of progranulin, levels of cathepsin D (both pro and mature) accumulate, although enzyme activity decreases, a key indicator of lysosomal dysfunction ( Götzl et al, 2018 ).…”
Section: Progranulinmentioning
confidence: 99%